2004
DOI: 10.1107/s0108270103028282
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Bipyridinium(1+) bromide monohydrate

Abstract: In the crystal structure of 2,2'-bipyridinium(1+) bromide monohydrate, C(10)H(9)N(2)(+).Br(-).H(2)O, the cation has a cisoid conformation with an intramolecular N-H.N hydrogen bond. The cation also forms an N-H.O hydrogen bond to an adjacent water molecule, which in turn forms O-H.Br(-) hydrogen bonds to adjacent Br(-) anions. In this way, a chain is formed extending along the b axis. Additional interactions (C-H.Br(-) and pi-pi) serve to stabilize the structure further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The nitrogen atoms N3, N4, and N5, as well as the pyridinium cation, form hydrogen bonds to H 2 O molecules. In the tetrazolide anion, the N−N distances lie between 1.328 (3) 36 The coordination compound [Sm(N 4 bipy) 2 (OH)(H 2 O) 2 ] (1) was obtained by refluxing 3 equiv. of HN 4 bipy with samarium(III) nitrate in isopropyl alcohol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The nitrogen atoms N3, N4, and N5, as well as the pyridinium cation, form hydrogen bonds to H 2 O molecules. In the tetrazolide anion, the N−N distances lie between 1.328 (3) 36 The coordination compound [Sm(N 4 bipy) 2 (OH)(H 2 O) 2 ] (1) was obtained by refluxing 3 equiv. of HN 4 bipy with samarium(III) nitrate in isopropyl alcohol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…respectively, which were both fully characterized including X-ray crystallography (the crystal structure of 2 was reported in ref. 14). Uchida et al 11d,12,15,16 have previously reported in closely related systems the formation of bipyridines from (1) the reaction of 2-pyridylphosphines or 2-pyridylphosphine oxides and chlorine followed by slow hydrolysis in alcohol or water and (2) the slow reaction of pyridylphosphine oxides or 1d with H 2 O (CH 3 OH) or H 2 O(CH 3 OH)/HCl, respectively.…”
Section: Synthesis and Properties Of [(2-py) 3 Pr]xmentioning
confidence: 96%
“…Кроме того, каркас хозяина bipy не способствует окислению гостевых молекул SO 2 кислородом воздуха, в отличие от систем с участием Tris [138], алкиламинов [139,140], бензиламинов [141] и гексаметилендиамина [139] (выделены и структурно охарактеризованы продукты «мягкого» окисления S(IV) в S(VI) -«ониевые» сульфаты). С другой стороны, заметно более сильные по сравнению с SO 2 •H 2 O минеральные кислоты (H 2 SiF 6 [142], HBr [143] и HClO 4 [144]) ожидаемо протонируют bipy с образованием соответствующих «ониевых» солей.…”
Section: ван-дер-ваальсовы клатратыunclassified